Potential uses of banana peelings: production of a bioplastic - López Giraldo, Javier; Cuarán Cuarán, Julio César; Arenas García, Laura Viviana; Flórez Pardo, Luz Marina (Revista Colombiana de Investigaciones Agroindustriales, 2014)
In 2006, in Valle del Cauca, 399.844 metric tons of banana peel, a poorly studied material, were produced. To study its value, a morphological, chemical and thermal characterization was effectuated; different tinctions were used to identify the different structures where the cellulose, lignine, lipids and starch are located. Subsequently, the content of extractibles was measured with a methanol-chloroform mixture, the cellulose, hemicellulose and ashes by the Van Soest method and Lignine by Klason. The thermal analysis was made through a TGA - thermogravimetrical analysis and DSC – Differential Scanning Calorimetry. It was found that the banana peel had a 11.91% of residual humidity, 23.03% of hemicellulose, 23.02% of cellulose, 29.87% of lignine and 0.78% of ashes, besides starch, observed by lugol tinction. The holocellulose content (hemicellulose and cellulose) is close to 46.05%, and makes it apt for papel elaboration while having less than 20% humidity and low ash content, making it useful for any thermal application with low environmental impact. However, we evidenced that by having a starch content close to 12%, is possible to obtain from it, a bioplastic. According to these results, studies were conducted to generate from this material, a particular use; a bio-paper and bio-plastic. With the first, the final product had a low mechanical resistance, while with the second, a biomaterial with positive results regarding durability and physical aspect. Para citar este artículo López, J., Cuarán, J., Arenas, L. y Flórez, L. (2014). Usos potenciales de la cáscara de banano: elaboración de un bioplástico. Rev. Colomb. Investig. Agroindustriales, 1(1), 7-21. DOI: http://dx.doi.org/10.23850/24220582.109